UKURAN PERUSAHAAN MEMODERASI PENGARUH PROFITABILITAS, SOLVABILITAS DAN OPINI AUDITOR TERHADAP AUDIT DELAY PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Amor Sofandi Aprilliant; Sri Wiranti Setiyanti; Edy Susanto; Marhamah Marhamah (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
This study aims to determine the effect of company size, profitability, solvency and auditor opinion on audit delay, and to determine the ability of company size to moderate the effect of profitability, solvency and auditor opinion on audit delay. This research is a quantitative study, with the study population being mining companies listed on the Indonesia Stock Exchange in 2016-2018. The sampling technique using purposive sampling technique obtained samples of 29 companies. Data collection uses the documentation method, with analysis techniques using multiple linear regression. The results of the study at the significance level of 5% indicate that: 1) profitability has no significant effect on audit delay, 2) solvency has a significant effect on audit delay, 3) auditor's opinion has no significant effect on audit delay, 4) company size has a significant effect on audit delay, 5) company size does not strengthen and weakens the effect of profitability on audit delay, 6) firm size does not strengthen and weaken the effect of solvency on audit delay, 7) firm size does not strengthen and weaken the influence of auditor opinion on audit delay.